KAJIAN NORMATIF GANTI KERUGIAN TERHADAP KORBAN SALAH TANGKAP DALAM PERSPEKTIF DUE PROCESS OF LAW - NIM. A1012201073, IZMI NAZILLA ASMIYANDHI (Fakultas Hukum Universitas Tanjungpura, 2026)
Indonesia, as a state based on the rule of law under Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, upholds the principle of due process of law within its criminal justice system. However, cases of wrongful arrest (error in persona) continue to occur, causing material, psychological, social, and reputational harm to innocent victims. This condition highlights the state's responsibility to provide compensation and rehabilitation. This study aims to analyze the mechanism for compensation and state responsibility for victims of wrongful arrest from the perspective of due process of law, as well as to examine the legal protection provided under the Indonesian Criminal Procedure Code (KUHAP) and Government Regulation Number 92 of 2015. This research employs a normative juridical method using statutory and legal synchronization approaches, with data analyzed descriptively. The findings indicate that KUHAP recognizes the right of wrongful arrest victims to obtain compensation and rehabilitation through pretrial proceedings. However, its implementation remains constrained by complicated procedures, short filing deadlines, limited compensation, and inadequate regulation of non-material damages. The case of Pegi Setiawan demonstrates that wrongful arrest also results in social stigma and reputational damage. Therefore, a more equitable, simple, and comprehensive compensation mechanism is needed to strengthen state responsibility and ensure the effective implementation of due process of law in Indonesia's criminal justice system. Keywords: Wrongful Arrest, Compensation, Legal Protection, Due Process Of Law Indonesia sebagai negara hukum berdasarkan Pasal 1 ayat (3) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 menjunjung tinggi prinsip due process of law dalam sistem peradilan pidana. Namun, praktik salah tangkap (error in persona) masih terjadi dan menimbulkan kerugian materiil, psikologis, sosial, serta reputasi bagi korban. Kondisi ini menunjukkan pentingnya tanggung jawab negara melalui pemberian ganti kerugian dan rehabilitasi. Penelitian ini bertujuan menganalisis mekanisme ganti kerugian dan tanggung jawab negara terhadap korban salah tangkap dalam perspektif due process of law, serta mengkaji perlindungan hukum berdasarkan KUHAP dan Peraturan Pemerintah Nomor 92 Tahun 2015. Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan sinkronisasi hukum yang dianalisis secara deskriptif-analitis. Hasil penelitian menunjukkan bahwa KUHAP telah mengatur hak korban untuk memperoleh ganti kerugian dan rehabilitasi melalui praperadilan. Namun, pelaksanaannya masih terkendala prosedur yang rumit, batas waktu pengajuan yang singkat, nominal kompensasi yang terbatas, serta belum optimalnya pengaturan kerugian immateriil. Studi kasus Pegi Setiawan menunjukkan bahwa dampak salah tangkap juga berupa stigma sosial dan rusaknya reputasi. Oleh karena itu, diperlukan reformulasi mekanisme ganti kerugian yang lebih adil, sederhana, dan komprehensif guna mewujudkan tanggung jawab negara dan penerapan due process of law secara efektif. Kata Kunci: Salah Tangkap, Ganti Kerugian, Perlindungan Hukum, Due Process of Law